Accessing European funds to develop rural entrepreneurship in Western Moldova - Alina-Mirela Marcu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The purpose of this scientific approach consists in analyzing the entrepreneurial initiatives from rural areas of Western Moldova, after Romania joined the European Union in the context in which the rural entrepreneurship has become in recent decades, the main source of income for an important segment of the rural population, especially for people made redundant or are unable to find a job. In pursuit of this work they were used statistical method and mapping method for expressing information acquired and for determining the spatial characteristics of projects beneficiaries with European funded. At regional level, the analysis indicates that private beneficiaries of the Fund for Agriculture and Rural Development were interested to carry out agricultural activities and crop and livestock farming, based on specific traditions Romanian village. To these are added investments for the acquisition of machinery and equipment for field crops, construction of sheds and purchase of animals. By accessing these European funds were supported mainly the small and medium enterprises, considered to be able to develop new products or to capitalize the natural resources through innovation and adaptation. Thus, the investments made were focused on increasing the competitiveness of the economy, the need to protect water resources and improve the quality of life of rural inhabitants of Western Moldova.
Keywords: 330; entrepreneurial initiatives; rural areas; beneficiaries; projects; resources